HERG channel trafficking: novel targets in drug-induced long QT syndrome. (25th October 2007) - Dennis, A.; Wang, L.; Wan, X.; Ficker, E.
Abstract : The cardiac potassium channel hERG (human ether - a - go - go -related gene) encodes the α-subunit of the rapid delayed rectifier current I Kr in the heart, which contributes to terminal repolarization in human cardiomyocytes. Direct block of hERG/ I Kr channels by a large number of therapeutic compounds produces acLQTS [acquired LQTS (long QT syndrome)] characterized by drug-induced QT prolongation and torsades de pointes arrhythmias. The cardiotoxicity associated with unintended hERG block has prompted pharmaceutical companies to screen developmental compounds for hERG blockade and made hERG a major target in drug safety programmes. More recently, a novel form of acLQTS has been discovered that may go undetected in most conventional safety assays. Several therapeutic compounds have been identified that reduce hERG/ I Kr currents not by direct block but by inhibition of hERG/ I Kr trafficking to the cell surface. Important examples are antineoplastic Hsp90 (heat-shock protein 90) inhibitors such as (i) geldanamycin, (ii) the leukaemia drug arsenic trioxide, (iii) the antiprotozoical pentamidine, (iv) probucol, a cholesterol-lowering drug, and (v) fluoxetine, a widely used antidepressant. Increased awareness of drug-induced hERG trafficking defects will help to further reduce the potentially lethal adverse cardiac events associated with acLQTS.